2022
DOI: 10.32598/sjrm.10.6.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Mindfulness-based Yoga Training Course on the Mental Toughness of Athletes With Different Skill Levels

Abstract: Background and Aims One of the critical variables affecting sports success is mental toughness, which is the ability to return from failure and imposed pressure. It seems that it is necessary to conduct interventional research on different sports communities and observe the effect of this intervention on different personality dimensions of athletes. Therefore, this study aimed to investigate the effect of a mindfulness-based yoga intervention on mental toughness in athletes with varying skill levels. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For instance, mindfulness training using breathing, meditation or yoga can increase the MT of athletes whether they are amateur participants, professionals or elite tennis players. 68 This, in turn, improves their mental health. 9…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, mindfulness training using breathing, meditation or yoga can increase the MT of athletes whether they are amateur participants, professionals or elite tennis players. 68 This, in turn, improves their mental health. 9…”
mentioning
confidence: 99%
“…For instance, mindfulness training using breathing, meditation or yoga can increase the MT of athletes whether they are amateur participants, professionals or elite tennis players. [6][7][8] This, in turn, improves their mental health. 9 Female athletes report higher rates of mental health symptoms and lower rates of mental well-being as reflected in their mindfulness, PWB and MT scores.…”
mentioning
confidence: 99%
“…It can not only improve the physical fitness of athletes, but also promote their physical and mental health, and attach importance to personal experience [ 9 ]. Mir Fatemeh explored the effects of different content, forms, and physiological loads of yoga and aerobic exercise on improving athlete physical fitness, and the results showed that long-term yoga practice was effective in improving athlete physical conditions [ 10 ]. Richmond Diane said that although yoga does not play an important role in improving the metabolism of athletes, it played a significant role in developing flexibility, strength, and reducing physical fatigue [ 11 ].…”
Section: Introductionmentioning
confidence: 99%